Epigenetic Regulation in Pathology of Atherosclerosis: A Novel Perspective - Tang, Haishuang; Zeng, Zhangwei; Shang, Chenghao; Li, Qiang; Liu, Jianmin (Frontiers in Genetics, 2021)
Atherosclerosis, characterized by atherosclerotic plaques, is a complex pathological process that involves different cell types and can be seen as a chronic inflammatory disease. In the advanced stage, the ruptured atherosclerotic plaque can induce deadly accidents including ischemic stroke and myocardial infarction. Epigenetics regulation, including DNA methylation, histone modification, and non-coding RNA modification. maintains cellular identity via affecting the cellular transcriptome. The epigenetic modification process, mediating by epigenetic enzymes, is dynamic under various stimuli, which can be reversely altered. Recently, numerous studies have evidenced the close relationship between atherosclerosis and epigenetic regulations in atherosclerosis, providing us with a novel perspective in researching mechanisms and finding novel therapeutic targets of this serious disease. Here, we critically review the recent discoveries between epigenetic regulation mechanisms in atherosclerosis.